The Influence of Leadership, Technology Acceptance and Training on Performance - Muhajirin, Adi; Hapzi Ali (Dinasti Publisher, 2023)
Literature Review Article the Effect of Leadership, Technology Acceptance and Training on Performance is a scientific article that aims to build a research hypothesis of the influence between variables that will be used in further research, within the scope of Human Resource Management science. The method of writing this Literature Review article is by library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this literature review article are: 1) Leadership affects performance; 2) Technology Acceptance affects performance; and 3) Training affects performance.